Brg1 Supports B Cell Proliferation and Germinal Center Formation Through Enhancer Activation - Schmiedel, Dominik; Hezroni, Hadas; Hamburg, Amit; Shulman, Ziv (Frontiers in Immunology, 2021)
Activation and differentiation of B cells depend on extensive rewiring of gene expression networks through changes in chromatin structure and accessibility. The chromatin remodeling complex BAF with its catalytic subunit Brg1 was previously identified as an essential regulator of early B cell development, however, how Brg1 orchestrates gene expression during mature B cell activation is less clear. Here, we find that Brg1 is required for B cell proliferation and germinal center formation through selective interactions with enhancers. Brg1 recruitment to enhancers following B cell activation was associated with increased chromatin accessibility and transcriptional activation of their coupled promoters, thereby regulating the expression of cell cycle-associated genes. Accordingly, Brg1-deficient B cells were unable to mount germinal center reactions and support the formation of class-switched plasma cells. Our findings show that changes in B cell transcriptomes that support B cell proliferation and GC formation depend on enhancer activation by Brg1. Thus, the BAF complex plays a critical role during the onset of the humoral immune response.